EFISIENSI PENEBANGAN KAYU DI KAWASAN HUTAN DENGAN SISTEM TEBANG PILlH INDONESIA (The efficiency of tree felling at the natural forest areas using the Indonesian selective cutting and planting system) - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1993)
An investigation of the efficiency of tree felling at forest areas using the Indonesian selective cutting and planting system (TPTI) was carried out at 5 logging companies in Central Kalimantan and 3 other companies in South Kalimantan in 1990. The objective is to find the way increasing the efficiency of tree felling at the natural production forests. For that purpose, data on felled tree volume, actually utilized logs and part of good logs left in the forest were collected. The investigationresults are as follows :1. Considering log diameter of 10 cm and up, the efficiency of improved felling technique can be increased by 6. 23 %.2. By using the improved felling technique, the volume of good quality clear bole logs is increased by 4. 90 %.3. The averages of stump heights between improved and existing felling techniques were 51.07 cm and 114.86 cm, respectively.4. the improved felling technique could increase the quality and volume of log for veneer (from 61.34% to 65. 83%) and for sawn timber (from 10.19 % to 10.45 %).5. It is necessary that the existing felling technical guidance and log administration be improved.